2021
DOI: 10.2147/ijgm.s242230
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Perioperative Neurocognitive Disorders (PND) Through Depth of Anesthesia Monitoring: A Critical Review

Abstract: General anesthesia has been administered for over 150 years, and in that time, has become progressively safer. Improvements in outcomes have been driven by multiple advances, including the use of non-invasive monitors to assess cardiovascular and respiratory status. More recent advances have included the development and use of monitors to measure neurologic status by means of "processed" electroencephalography (pEEG), wherein the frontal EEG signal is analyzed by proprietary algorithms to produce a dimensionle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 68 publications
0
26
0
3
Order By: Relevance
“…Some may prefer to avoid the need for vasopressors and give smaller, incremental doses of propofol, others are more concerned about hypertension, tachycardia, and awareness and will administer larger doses of propofol although some may be worried about the long-term effects of deep anesthesia. [4][5][6] In sum, this is a fascinating report, and it provides excellent insight into the range of total propofol doses used during induction in actual patients. Nevertheless, it does not tell us which bolus dose we should start with when inducing a patient with propofol.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Some may prefer to avoid the need for vasopressors and give smaller, incremental doses of propofol, others are more concerned about hypertension, tachycardia, and awareness and will administer larger doses of propofol although some may be worried about the long-term effects of deep anesthesia. [4][5][6] In sum, this is a fascinating report, and it provides excellent insight into the range of total propofol doses used during induction in actual patients. Nevertheless, it does not tell us which bolus dose we should start with when inducing a patient with propofol.…”
mentioning
confidence: 84%
“…Finally, clinicians may vary subjectively in what they want propofol to accomplish. Some may prefer to avoid the need for vasopressors and give smaller, incremental doses of propofol, others are more concerned about hypertension, tachycardia, and awareness and will administer larger doses of propofol although some may be worried about the long‐term effects of deep anesthesia 4–6 …”
mentioning
confidence: 99%
“…Examples of peri‐operative care bundles have included: the Hospital Elder Life Program (orientation, nutritional support, early mobilisation) after abdominal surgery [4]; and a multidisciplinary approach to hip fracture surgery (fascia iliaca blocks, rationalising prescribing practices and avoidance of triggers) [5]. Investigations of single interventions have included: benzodiazepine restriction [6]; intra‐operative use of the inhalational anaesthetic agent, xenon [7]; depth of anaesthesia monitoring [8]; and dexmedetomidine given at various time‐points in the peri‐operative period [9].…”
Section: Pathophysiology Of Postoperative Deliriummentioning
confidence: 99%
“…Though some retrospective studies have demonstrated correlation between increased depth of anesthesia and delirium, recent randomized control trials have been more circumspect about that association [27,28]. Titration of anesthetics, using depth of anesthesia monitors in elderly patients, has not been able to show conclusively a decrease in the incidence of delirium or postoperative neurocognitive dysfunction [28].…”
Section: Current Practice Pattern Of Anesthetic Drug Dosing With Agingmentioning
confidence: 99%
“…Though some retrospective studies have demonstrated correlation between increased depth of anesthesia and delirium, recent randomized control trials have been more circumspect about that association [27,28]. Titration of anesthetics, using depth of anesthesia monitors in elderly patients, has not been able to show conclusively a decrease in the incidence of delirium or postoperative neurocognitive dysfunction [28]. However, using well-established decreased dosing regimens of anesthetics in elderly would be prudent practice, as it may avoid other complications such as hypotension, respiratory depression, or delayed recovery.…”
Section: Current Practice Pattern Of Anesthetic Drug Dosing With Agingmentioning
confidence: 99%